Thyroid Under Siege: A Rare Manifestation of Breast Cancer Metastasis - Fatima Yousaf; Ayesha Zubair; Hajira Ilyas (Journal of the Pakistan Medical Association, 2025)
Breast cancer is the most frequently diagnosed cancer in women all over the world and commonly metastasizes to lymph nodes, bones, lungs liver and brain. There is a slight increase in incidence of second primary malignancy in thyroid gland of patients with breast cancer. However, thyroid gland is a rare site of breast cancer metastatic spread. We present a rare case of breast carcinoma with incidental uptake on F18-FDG PET-CT which was histologically confirmed to be metastatic breast carcinoma to thyroid gland. Keywords: Breast cancer, thyroid gland metastasis, F-18 FDG PET-CT.